Comparative Analysis of the Results of Traditional and New Distance Learning Method Among the Master’s Degree Students and Physicians in Uzbekistan - Zokhid Abdurakhimov (Institute of Medico-legal Publications Pvt Ltd, 2020)
The rapid changes in medical theory and practice require physicians to undertake continuing medicaleducation. The low level of qualifications of physicians can eventually lead to medical errors. There is aspecial currency to measure and evaluate the obsolescence of knowledge, the so-called half-life of knowledge.Materials and Method: Analysis of results and evaluations using various forms of training method onone topic between 2nd year master’s degree students (masters) of Tashkent pediatric medical institute andphysicians. Training was conducted traditionally (face-to-face form for periods of each time 1 hundred 10minutes) and distance-based (internet point of-care learning and journal-based continual medical education).The results of tests among 72 masters and 84 physicians were retrospectively analyzed.Results: According to the study, it was found that the average rating in the group of Masters via traditionalmethod with an “unsatisfactory” evaluation was 2 (4%) while in the group of physicians with the sametest the number with an unsatisfactory evaluation was 9 (21%), (which is four times more). The number ofMasters who received a satisfactory evaluation was 12 (23%) (18 physicians received the same evaluation,representing 43%). The number of Masters who got a good evaluation was 23 (43%) and only 10 or 24 %of the physicians got the same score (which is twice less than the result of masters) and 16 (30%) Mastersreceived an excellent rating (5 physicians received the same mark or this was 3 times less).Discussion: More than half of the physicians (being 27 or 64%) responded to the test with an evaluationof “satisfactory” and “unsatisfactory”, while only 14 (26% or 2.5 times less) Masters received such marks.Only 15 (35%) physicians received “good” or “excellent” rating, whereas among the masters, this result was39 (60% or 2 times higher than the responses of physicians). However, among the participant soft the onlineprogram unsatisfactory response was not observed. 8 (42%) participants answered satisfactorily, 11 (58%)of the participants responded with good or excellent marks.Conclusions: Following the results of the analysis, the study showed that the increase in theoreticalknowledge has been identified in a larger number of masters. The knowledge gained through traditionalteaching or distance (online and journal form of training) learning, seems virtually identical, and the studyseems to indicate that they even surpass the traditional method of training.